Strengthening, Corrosion and Protection of High Temperature Structural Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
High-temperature structural materials are characterized by their high melting point, high-strength and high-temperature creep resistance, low thermal expansion coefficient, and excellent corrosion resistance. Such materials are widely used in metallurgy, chemical applications, aerospace, nuclear reactors, and other situations where extreme environments are encountered. During high-temperature service, high-temperature structural materials are exposed to extremely harsh high-temperature environments, bear mechanical and thermal loads, and are exposed to high-temperature oxidation, erosion, corrosion, etc. Therefore, high stress can be easily concentrated at a defect site, especially near the phase interface. Thermal expansion stress will drive the nucleation and propagation of cracks. At the same time, friction, oxidation, and corrosion will also aggravate crack propagation and material failure, which will pose a catastrophic threat to high-temperature components. Therefore, the characterization, understanding, strengthening, and corrosion protection of high-temperature structural materials are very important. This Special Issue focuses on second phase enhancement, surface coating technology, high-temperature corrosion, wear, erosion, and protection with respect to high-temperature structural materials.